Identifikasi Epidermophyton Sp. pada Penyakit Onychomycosis Penyebab Infeksi Kuku dengan Analisis Mikologi Laboratorium dan Diagnosis Morfologi Jamur - Devina Adira Azzahra; Desi Rahmasari; Feni Atika Tsuroyya; Nasywarana Putri Panjaitan; Rizka Fellithia; Septi Puspita Kurniawati; Liss Dyah Dewi Arini (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Epidermophyton floccosum is the only pathogenic species within the genus Epidermophyton, classified as a dermatophyte and recognized as one of the causative agents of toenail onychomycosis. Onychomycosis caused by E. floccosum is characterized by nail plate thickening, yellowish-to-brownish discoloration, subungual hyperkeratosis, and onycholysis of a chronic, non-self-resolving nature. This study aims to comprehensively review the mycological characteristics, epidemiology, pathogenesis, clinical features, diagnosis, and management of toenail onychomycosis caused by Epidermophyton floccosum based on original scientific journals published between 2021 and 2026. A literature review was conducted on PubMed, EMBASE, Scopus, and Wiley Online Library databases using the keywords Epidermophyton floccosum, Onychomycosis, Dermatophytosis of the nails, Dermatophytes, and Fungal nail infection. Results indicate that E. floccosum is an anthropophilic fungus transmitted through direct contact on moist communal surfaces, predominantly found in tropical and subtropical regions. Morphologically, it is characterized by club-shaped macroconidia with smooth thin walls, the absence of microconidia, and the production of keratinase enabling invasion of keratinized nail tissue. The prevalence of E. floccosum among confirmed dermatophytosis cases reached 1.8%, with annual variation of 0.4%–3.0%, and higher rates in tropical and subtropical areas. Key risk factors include use of moist communal facilities, immunosuppression, diabetes mellitus, and poor foot hygiene. Management with oral terbinafine or itraconazole requires ≥12 weeks of therapy, with significant recurrence risk. These findings underscore the importance of accurate species identification in onychomycosis management to optimize treatment outcomes.